De-Strategizing Paradigm in Strategic Management: The Philosophical Foundations - Eskandarinia, Nima (International journal of industrial engineering and operational research, 2023)
Different theories of competitive advantage can be attributed to one of five common paradigms including resource-based view, industrial organization approach, entrepreneurial perspective, transaction cost approach and behavioral perspective. Each of these paradigms has its own philosophical foundations. In other words, all these paradigms are different from each other in terms of logic, axiology, ontology, epistemology and methodology. In recent years, some scholars have made fundamental criticisms to the scientific structure and theoretical hypothesis of competitive advantage and strategic management. Therefore, the purpose of this research is the philosophical analysis of the current competitive advantage paradigms, as well as the philosophical analysis of the criticisms of strategic management theories and finally the introduction of a new paradigm under the title of de-strategization. In order to conduct this research, the method of qualitative content analysis of articles has been used. The qualitative content analysis of the articles that criticized the science of strategy and the theories of competitive advantage continued until reaching theoretical saturation, and the collection of articles was also selected by purposeful sampling based on the degree of suitability with the purpose of the research. The findings of this research show that a new paradigm that is different from the five existing paradigms in terms of logic, axiology, epistemology, ontology and methodology is being formed. In this new paradigm, unlike all five previous paradigms, the definitive and linear relationship between the three components including strategy creation, gaining competitive advantage and achieving premium performance is challenged. In addition, in the paradigm of de-strategization, not only the competitive advantage does not have a strong link with the success of the organization, but there are evidences about the organizations without competitive advantage and even with a competitive disadvantage, which were able to achieve success and desired performance.